Un sogno a occhi aperti - Vari, Autori (Il sogno della farfalla, 2005)
The article collects the speeches and the debate which took place for the occasion of the presentation of the 4° issue 2004 of "Il sogno della farfalla", at the national small and medium-size publisher’s Fair held in Rome on 10° December 2004. The talks dealt wuth three fundamental points: 1) the history of the magazine, which is part of the history of the Collective Analysis and the development of M. Fagioli’s theory on mental illness as a psychic phenomenon, taking this as the permises of its widely interdisciplinary approach; 2) the political value that Fagioli’s theory and practice have taken on from their origins, in their fierce opposition to Freud’s reactionary ideology and to Marx’s annulment of man’s psychic reality; 3)the research into the physical and mental reality of human beings. Among other things we witness the emergence of a new method of thinking which goes beyond the simple positivist observation of the facts, and allows us to study human psychic reality. Ando so on this basis, the research into the various transformations tha allow the rise of a distinctive human reality is focused, beyond the caesura of birth when the first interior image appears, into the passage from 23rd week of pregnancy when the foetus begins to be potentially vital.